(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A herbarium is a storehouse of plant specimens which are collected, dried and mounted on handmade paper sheets. They will be organized in plant families perceived system of characterization and kept in pigeon holes of steel or wooden cup boards and kept up carefully for present and future investigations. It is a reference material for naming, identification and order of the plants. With increment in way of life and intra transferable disorders, similar to hypertension, diabetes, asthma and numerous others individuals slanted towards the Ayurvedic medicine. Numerous little pharmaceutical organizations are developing for the satisfaction of the above interest. It is important to produce plan of medicine ought to be standard and according to portrayed in the traditional content. The specialist of old times used to collect medicinal plants from timberland themselves, some of them used to develop medicinal plants around their center. This training used to guarantee them of the utilization of right plant. In any case, these days vaidyas started to recommend medicines, and they are completely relied upon producers. In this circumstance, it is mandatory to build up the herbarium that helps in the identification of medicinal plants.